Inflammatory Breast Cancer at Stage T4dN2aM0 – Efficacy of Neoadjuvant Therapy Based: A Case Report - Czyż, Sandra; Marszał, Wiktoria (Journal of Education, Health and Sport, 2026)
A case of a 64-year-old female patient diagnosed with left-sided inflammatory breast cancer at stage T4dN2aM0 was described. Histopathological examination revealed grade 3 invasive ductal carcinoma, negative for hormonal receptor expression (ER−, PR−), with HER2 overexpression (3+) and a high Ki-67 proliferation index (85%). Metastatic involvement of the axillary lymph nodes was present. Neoadjuvant therapy was administered, resulting in a partial clinical response. Subsequently, a modified radical mastectomy according to the Madden technique was performed. Postoperative histopathological assessment demonstrated no residual carcinoma within the breast (ypT0); however, metastatic involvement was confirmed in 5 lymph nodes (ypN2a). Adjuvant treatment included trastuzumab and radiotherapy. During follow-up, no evidence of local recurrence or distant metastases was observed. Extended genetic testing did not identify mutations associated with hereditary cancer predisposition.